Patterns, Perceptions, and Academic Implications of Social Media Use among Tertiary Institution Students in Yobe State, Nigeria - Ciroma, Zainab Ibrahim; Abubakar, Abdulkadir Musa; Bashir, Abdulkarim Bello (African Multidisciplinary Journal of Sciences and Artificial Intelligence, 2025)
The increasing use of social media among Nigerian undergraduates presents a paradox in academic performance. While platforms such as WhatsApp, Facebook, and YouTube offer opportunities for academic collaboration, access to educational materials, and professional networking, their unregulated use often results in poor time management, reduced concentration, and decreased study commitment. This issue is particularly relevant in Yobe State, where access to higher education is expanding rapidly, underscoring the need to balance digital engagement with academic responsibilities. This study employed a comparative survey design, focusing on undergraduates from Federal Polytechnic Damaturu and Yobe State University. Data were collected to examine patterns of social media usage, students’ perceptions of its academic utility, and its relationship to self-reported academic performance. Findings revealed that although many students acknowledged the academic benefits of social media, including enhanced collaboration and rapid information access, a significant proportion admitted to using these platforms primarily for non-academic purposes. This imbalance was linked to procrastination, inconsistency in study habits, and reduced academic productivity. The study concludes that social media is not inherently beneficial or detrimental; its impact depends on usage patterns and the degree of user self-regulation. The findings highlight the need for short-term digital literacy interventions, institutional policies, and awareness campaigns aimed at promoting responsible social media use to enhance academic outcomes while mitigating potential drawbacks.